Neighborhood influences on violent reoffending risk in released prisoners diagnosed with psychotic disorders - Sariaslan, A; Larsson, H; Lichtenstein, P; Fazel, S (Oxford University Press, 2017)
Released prisoners diagnosed with psychotic disorders have elevated rates of violent reoffending risk and their exposure to adverse neighborhood environments may contribute to this risk. We identified all released sentenced prisoners in Sweden between 2003 and 2013 (n=47,226) and followed them up for a median period of 4.4 years. We identified prisoners who had ever been diagnosed with a psychotic disorder (n=3782) or prescribed antipsychotics (n=7366). We examined three neighborhood characteristics: income, proportion of welfare recipients, and crime rate. By fitting generalized mixed-effects and negative binomial regression models and adopting within-individual designs that controlled for all time-invariant unmeasured confounders within each individual, we estimated neighborhood intra-class correlations (ICCs) and associations between specific neighborhood characteristics and violent reoffending. Neighborhood factors explained 13.5% (95% CI: 10.9%-16.6%) of the violent reoffending risk among released prisoners diagnosed with psychotic disorders. This contrasted with 4.3% (95% CI: 3.7%-4.9%) in all released prisoners. However, after controlling for unmeasured confounding, these estimates were not statistically significant (ICCpsychotic disorders=0.9%; 95% CI: -0.8%-2.3%; ICCall prisoners=0.3%; 95% CI: -0.02%-0.6%). Similarly, none of the within-individual correlations between the specific neighborhood factors and violent reoffending were significantly different from zero. We found consistent results when we investigated prisoners with other psychiatric and substance use disorders. These findings suggest that placing released prisoners with psychotic disorders in less deprived neighborhoods might not reduce their violent reoffending risk, which may also apply to other psychiatric disorders. The assessment, treatment and community linkage of high-risk prisoners as a strategy to reduce reoffending needs further research.